El análisi finaciero de la Unidad Educativa Particular Santa Mariana de Jesús del Cantón Riobamba y su incidencia en la toma de desiciones, período 2014. - Pacheco Trávez, Flor Elizabeth (2016)
The research entitled “FINANCIAL ANALYSIS AND ITS IMPACT ON DECISION MAKING AT EDUCATIONAL UNIT SANTA MARIANA DE JESUS Riobamba during 2014” was developed to establish results relation and application of financial analysis methods with taking making in the school during the study period. The research method used was the inductive, the design was not experimental; it was field and documentary research and the investigation level was diagnosis. For obtaining information, observation techniques and interviews with their respective instruments were used. Taking as reference theoretical framework for research variables, the contrasting financial statements are analyzed vertically and horizontally to establish trends in overall growth finances; and the relation among groups of different accounts involved in reporting both progress and results. The conclusions and recommendations emerged of analysis financial information and applied techniques results, and the proposal to improve decision-making in the institutional financial sector